Pemanfaatan Tanah TPA Terjun terhadap Pertumbuhan Tanaman Lavender (Lavandula Angustifolia) - Panjaitan, Delima; Sulastri, Yustina Sri; Saitararak, Oktaria (AGROSUSTAIN, 2025)
This research aims to determine the effect of the quantity and distance of land collection from the Terjun Landfill and the effect of the interaction of these two treatments on the growth of lavender plants (Lavandula angustifolia). Landfill soil is land in a final disposal site where, in this soil the organic nutrient content is quite high, but you need to know that apart from organic waste in landfill land there is also electronic waste, resulting in metal elements contained in landfill soil being also quite high. This research was carried out in screen house, Faculty of Agriculture, Santo Thomas Catholic University, Medan, with an altitude of 32 meters above sea level starting from February to April 2024. This research used a randomized block design (RAK) with 2 factors. The first factor is the distance to take landfill land (J) which consists of 3 levels, namely: J1= 0 m, J2= 52 m, J3= 104 m. The second factor is the quantity of landfill soil (M) consists of four levels, namely M1 = without landfill soil (Control), M2 = 3 kg, M3 = 4 kg, M4 = 5 kg. Data analysis uses analysis of variance. The parameters observed were plant height, number of shoots, root wet weight, root dry weight, root volume, shoot wet weight and soil pH. Based on the research results, it can be stated that the distance factor for taking soil has a very significant influence on plant height, number of shoots, root volume and wet weight of lavender plant crowns. The quantity of soil has a significant effect on plant height and the interaction between the distance from the landfill and the quantity of landfill soil has a significant effect on the wet weight of the canopy.